Enhancing Breastfeeding Self-Efficacy through Counselling: Focus on Early Initiation and Exclusive Practices - Mulia Sakti, Putri; Hasnawati; Sumiaty (Public Health of Indonesia, 2025)
Background:Both high- and low-income countries face challenges related to inadequate breastfeeding practices, which are influenced by maternal self-efficacy in nursing. Breastfeeding counseling has been identified as a potential intervention to address this issue. Objectives:This study aimed to enhance maternal breastfeeding self-efficacy through counseling interventions to promote early initiation and exclusive breastfeeding practices. Method:This study employed a one-group pre-test and post-test research design. The sample comprised third-trimester pregnant women selected using purposive sampling. Inclusion criteria were as follows: gestational age of at least 34 weeks, primigravida status, singleton pregnancy, absence of breast abnormalities, and non-smoking or non-alcohol-consuming mothers. Mothers and/or infants requiring special care were excluded. Data collection was conducted using the Breastfeeding Self-Efficacy Scale-Short Form (BSE-SF) questionnaire. Statistical analysis included paired t-tests for normally distributed data and Wilcoxon signed-rank tests for non-normally distributed data, with a significance threshold set at p-value < 0.05. Result: The findings indicated a significant increase in maternal breastfeeding self-efficacy following the counseling intervention. Conclusion:Higher levels of breastfeeding self-efficacy were associated with increased maternal confidence in initiating and maintaining early and exclusive breastfeeding. This confidence helped mothers overcome various challenges encountered during the breastfeeding process.  Keywords:breastfeeding; counseling; self-efficacy; maternal health; Indonesia